Effects of double qualifications on various dimensions of job satisfaction - Bellmann, Lutz [Verfasser]; Stephani, Jens [Verfasser] (My University, 2012)
"Using a sample of graduates from a unique employee survey, this paper analyses the individual effects of double qualifications, i.e. of first taking up vocational training after obtaining the German upper secondary school-leaving certificate (Abitur) instead of going straight on to university. Our estimations take into account the potential endogeneity of having a double qualification. We find that the effects of double qualifications on wages and on eleven single dimensions of job satisfaction are either significantly positive or insignificant, but never significantly negative. Our results suggest that individual risk considerations are of minor importance in the context of double qualifications; however, such complex educational paths provide valuable labour market information for individuals." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.4 Doppelqualifizierende Bildungsgänge; G 1.3.3.1 Qualifikationsverwertung; Doppelqualifikation; Bildungsertrag; Einkommen; Arbeitszufriedenheit; Empirische Forschung